1994
DOI: 10.1021/ma00094a012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Soluble Aromatic Polyesters Containing Oligophenyl Moieties in the Main Chain

Abstract: A series of rigid aromatic polyesters containiig substituted oligophenyls wasprepared. Aliphatic and aromatic side groups were used to increase the solubility. New oligophenyldiols were synthesized by coupling aromatic Grignard reagenta with aromatic halides, using palladium complexes as catalysta. The polyesters were prepared by melt polycondensation and characterized by viscosimetry, thermal analysis, and dynamic mechanical analysis. The temperature dependence of the intrinsic viscosity, in the range 30-85 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…14 -16 A comparison of the mechanical properties behavior of the system studied here with that of another polyester, studied by Kallitsis,14,15 showed that the main difference was the relatively high temperature of ␤ transition appearing in the relatively short side chain (methyl group) in this article. In addition, the glass transition at around 225°C is associated with an approximately 2 orders of magnitude decrease in GЈ.…”
Section: Polymer Characterizationmentioning
confidence: 80%
“…14 -16 A comparison of the mechanical properties behavior of the system studied here with that of another polyester, studied by Kallitsis,14,15 showed that the main difference was the relatively high temperature of ␤ transition appearing in the relatively short side chain (methyl group) in this article. In addition, the glass transition at around 225°C is associated with an approximately 2 orders of magnitude decrease in GЈ.…”
Section: Polymer Characterizationmentioning
confidence: 80%
“…Chemicals were purchased from Aldrich and used as received unless otherwise specified. 2,5‐Dialkoxy‐1,4‐phenyldiboronic acids,29 2,5‐dialkyl‐1,4‐phenyldiboronic acid,30 2′,3′,5′‐triphenyl‐ p ‐terphenyl‐4‐4″‐diol,31 2″,3″,5″‐triphenyl‐ p ‐quinquephenyl‐4‐4″″‐diol,31 2′,5′‐dihexyloxy‐ p ‐terphenyl‐4‐4″‐diol,32 2″,5″‐dihexyloxy‐ p ‐quinquephenyl‐4‐4″″‐diol,18 4‐acetoxybromobenzene, 4‐acetoxy‐4′‐bromobiphenyl,33 and bis(fluorophenyl)phenylphosphine oxide34 were synthesized according to reported procedures. Dimethylformamide (DMF) was distilled and kept under molecular sieves.…”
Section: Methodsmentioning
confidence: 99%
“…But their poor solubility in organic solvents often restricts its use for many applications. Thus, it is clear that various structural changes should be made in the poly(azomethine ester)'s chain to obtain better solubility and its application in various fields [9][10][11][12][13][14][15]. Some of the reported methods to improve the processability of conjugated poly(azomethine)s are by incorporation of unsymmetrical or symmetrical substitutions in the main-chain aromatic benzene rings with flexible alkyl or alkoxy side chains and reversible Lewis acidbase complexation [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%